Renal resistive index in obese and non-obese cats - de Souza, Fúlvia Bueno [UNESP]; Gonçalves, Natália Volpi [UNESP]; Bonatelli, Shayra Peruch [UNESP]; Belotta, Alexandra Frey [UNESP]; Geraldes, Silvano Salgueiro [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Guimaraes-Okamoto, Priscylla Tatiana Chalfun [UNESP]; Lourenço, Maria Lúcia Gomes [UNESP]; Ramos, Paulo Roberto Rodrigues [UNESP]; Rahal, Sheila Canevese [UNESP]; Melchert, Alessandra [UNESP] (My University, 2022)
This study aimed to compare renal function between obese and normal-weight healthy cats, using intrarenal resistive index (RI), serum symmetric dimethylarginine (SDMA), and serum creatinine, and to identify the variables that might influence intrarenal RI. Thirty crossbred client-owned cats met the inclusion criteria and were allocated into two groups: Control and Obese. Body weight, body mass index (BMI), body condition score (BCS), SAP, serum SDMA, urea, and creatinine were evaluated. B-mode and Doppler ultrasound of the kidneys were done. RI evaluation was in the interlobar artery. SDMA and intrarenal RI were compared between groups, also considering the gender of the cats. A correlation analysis between intrarenal RI with the other parameters was performed. SDMA was higher in the Obese group. Intrarenal RI was higher in females than males in the Obese group. Obese females presented higher RI and SDMA than Control females. A positive correlation was observed between RI, age, body weight, and BMI. Six obese cats (40%) showed increased RI. The increase in body weight, BCS, and BMI resulted in a simultaneous increase in RI and SDMA. The RI may assist in monitoring renal function, and may be associated with preclinical kidney changes in obese cats.
Keywords: Body condition score; Domestic cats; Doppler; Kidney; Resistive index